Priročnik za delo s programom za optimiranje sovprežnega stropnega sistema s plastično odpornostjo nosilca z jeklenimi IPE profili: COMBOPT-PIPE, verzija 1,0 - Žula, Tomaž; Kravanja, Stojan (University of Maribor Press, 2024)
Manual for Working With the Program for Optimizing the Composite Floor System With the Plastic Resistance of the Beam With Steel Profiles IPE: COMBOPT-PIPE, version 1,0. The manual presents the work with the program for optimization of the composite floor system, which can be used in the structure of multi-storey buildings. The structure consists of a reinforced concrete slab and IPE steel profiles. Mixed integer nonlinear programming (MINLP) is used for optimization. A COMBOPT-PIPE optimization model was developed with a detailed objective function of the self-manufacturing costs. In addition to the objective function, the optimization model also includes input data, variables, (in)equality constraints known from the dimensioning of composite structures and logical constraints. Dimensioning constraints are defined according to Eurocod